Stress dependence of microstructures in experimentally deformed calcite. (December 2017) - Platt, John P.; De Bresser, J.H.P.
Abstract: Optical measurements of microstructural features in experimentally deformed Carrara marble help define their dependence on stress. These features include dynamically recrystallized grain size ( Dr ), subgrain size ( Sg ), minimum bulge size ( Lρ ), and the maximum scale length for surface-energy driven grain-boundary migration ( Lγ ). Taken together with previously published data Dr defines a paleopiezometer over the range 15–291 MPa and temperature over the range 500–1000 °C, with a stress exponent of −1.09 (CI −1.27 to −0.95), showing no detectable dependence on temperature. Sg and Dr measured in the same samples are closely similar in size, suggesting that the new grains did not grow significantly after nucleation. Lρ and Lγ measured on each sample define a relationship to stress with an exponent of approximately −1.6, which helps define the boundary between a region of dominant strain-energy-driven grain-boundary migration at high stress, from a region of dominant surface-energy-driven grain-boundary migration at low stress. Highlights: We define a revised calcite paleopiezometer with a stress exponent of −1.09. Subgrain size and dynamically recrystallized grain size are the same within uncertainty. We see no evidence for grain growth after nucleation by BLG or SGR mechanisms. We define a scale length for surface energy driven grain-boundary migration ( Lγ ). The minimum bulge size and Lγ define a line with a stress exponent of about −1.6.